Effects of Menstrual Cycle on the Accumulation of Human Papillomavirus-Infected Cells Exfoliated from the Cervix That Drift into the Vagina - Mitsuaki Okodo; Kaori Okayama; Koji Teruya; Kazumasa Tanabe; Chieko Ito; Yasuyoshi Ishii; Masahiko Fujii; Hirokazu Kimura; Mizue Oda (Microorganisms, 2022)
Human papillomavirus (HPV) testing using self-collected vaginal specimens is the preferred choice to increase screening uptake. Although the HPV testing results of these samples depend on the cells that naturally exfoliate from the cervical lesion and drift into the vagina, the mechanism of when and how these exfoliated cells mix with the self-collected sample remains unclear. Hence, the study aimed to clarify the relationship between the vaginal drift of HPV-infected cells exfoliated from the cervix, and the menstrual cycle. A total of 180 scraped samples of the cervix and vagina were examined. The exfoliated cells were classified into two categories according to the HPV genotyping results of each sample: sufficient accumulation (same HPV types in cervical and vaginal samples) and insufficient accumulation (fewer HPV types in vaginal samples than in cervical samples, or HPV positivity in cervical samples and HPV negativity in vaginal samples). A moderately strong statistically significant association was observed between exfoliated cell accumulation and the menstrual cycle, and insufficient accumulation was statistically significantly increased at the early proliferative phases. Self-collection of vaginal samples at the early proliferation phase indicates insufficient sample quantities or lower viral load, thereby affecting HPV genotyping.